Kapabilitas Pemasaran Absorptif, Adaptif, dan Inovatif terhadap Kinerja Pemasaran pada Online Shop Pakaian Wanita di Instagram - Elia Resha Fatmawati; Sentot Suciarto Athanasius (Universitas Katolik Soegijapranata, Semarang, 2020)
This study aims to analyze the effect of absorptive marketing capabilities, adaptive marketing capabilities, and innovative marketing capabilities to marketing performance simultaneously and partially on women's clothing online shops on Instagram. Respondents in this study were the owners of women's clothing online shop on Instagram, amounting to 96 respondents. This research was conducted quantitatively by testing the hypothesis using multiple regression that showed the results of the capabilities of absorptive, adaptive, and innovative marketing simultaneously had significant effect on marketing performance; but partially only innovative marketing capabilities had significant effect on marketing performance.